Bone mineral content and body size 65 to 100 weeks' postconception in preterm and full term infants. Issue 11 (November 1989) - Horsman, A; Ryan, S W; Congdon, P J; Truscott, J G; Simpson, M
Abstract : A total of 36 preterm and 22 full term infants were weighed and measured at 65 to 100 weeks' postconception. It was found that the preterm infants were on average significantly lighter by 1008 g and shorter by 3.8 cm than those born at full term. Despite the smaller size of preterm infants, mean values of bone mineral content in the mid-forearm were not significantly different between the two groups. In contrast, near 40 weeks' postconception the mean bone mineral content observed in 35 of the preterm infants was significantly smaller than that observed in eight of the full term infants. Our results suggest that there is a phase of rapid mineral accretion between 40 and 60 weeks' postconception. This 'catch up' in mineral accretion reduces the perinatal mineralisation deficit that might otherwise persist into childhood.